Solution stability of active materials for organic photovoltaics. (March 2015) - Yang, Junliang; Clark, Noel; Long, Mengqiu; Xiong, Jian; Jones, David J.; Yang, Bingchu; Zhou, Conghua
Highlights: P3HT, PCBM, and P3HT:PCBM blend solutions have different stabilities, and influence the device performance differently. These solutions are much more stable than P3HT, PCBM, and P3HT:PCBM in thin film form. P3HT:PCBM blend solution can be stable over two months, much more stable than P3HT or PCBM solutions stored separately. P3HT and PCBM could stabilize each other in their blend solution resulting from the formation of P3HT:PCBM dimers. It provides a new understanding of the solution stability of active materials, and has great practical applications. Abstract: The solution stability of the active materials poly(3-hexylthiophene) (P3HT), [6, 6]-phenyl C61 butyric acid methyl ester (PCBM), and P3HT:PCBM blends were studied by a combination of organic photovoltaic (OPV) device performance, ultraviolet–visible ( uv – vis ) spectroscopy, and simulation calculations. OPV devices based on the structure ITO/PEDOT:PSS/Active layer (P3HT:PCBM)/Al showed that pure P3HT, pure PCBM, and P3HT:PCBM blend solutions could be stable for as long as one month when stored in either a glovebox or in air. Especially, P3HT:PCBM solution blends are much more stable than P3HT or PCBM solutions stored separately, in which the former could be stored stably over two months. The addition of PCBM to P3HT solution forms P3HT:PCBM dimers, avoiding the formation of charge transfer complexes. The calculation results showed that the electronic wave-function of highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are isolated in P3HT:PCBM dimers. The research provides a new understanding on the stability of P3HT and P3HT:PCBM solutions, and has great practical application in the fabrication of large-area OPV modules by printing or coating techniques.